The Contrast of Cholesteric-Nematic Transition in Indused Cholesterics - A, Fechan; J, Semenova; D, Batbayarin; O, Batbayarin (Scientific transaction of the National University of Mongolia. Physics, 2022)
The contrast characteristics of cholesteric-nematic transition (CNT) in nematic-cholestric mixtures with a low (up to 2weight %) optical active dopant content were analysed.